Unusual MR and CT appearance of an epidermoid tumor. - Gualdi, G F; Di Biasi, C; Trasimeni, G; Pingi, A; Vignati, A; Maira, G (American Journal of Neuroradiology, 1991)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf